The Impact of Dark-Rearing on Auditory Enhancement of Visual Detection and Localization - Smyre, Scott Alexander (Wake Forest University, 2019)
Multisensory neurons in the superior colliculus develop their ability to integrate cross-modal cues over time. Physiological studies have been conducted on cats looking at the consequences of removing early sensory experiences on the maturation of these neurons. These studies show that multisensory neurons fail to develop their integrative capabilities. The behavioral consequences of this lack of integrative capabilities have not been examined. To observe these consequences, animals were raised in the absence of visual cues and then tested in a detection and localization paradigm. These animals were found to not exceed statistical facilitation in the cross-modal condition. This suggests that the physiological consequences predict the responses to these stimuli in awake behaving animals.